Sur la stratification des complexes de droites - Vaškas, P. (Lithuanian Mathematical Journal, 1963)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:П. Вашкас. О расслоении комплексов прямыхP. Vaškas. Apie tiesių kompleksų išsluoksniavimą